الاتجاه نحو التخصص و علاقته بالتوافق الدراسي لدى تلاميذ السنة أولى ثانوي دراسة ميدانية بثانويتي أحمخد قصيبة و أول نوفمبر بمدينة الأغواط - صونية طرفاية; مريم سعودي; شلالي لخضر (My University, 2018)
The aim of the current study to know the relationship between the tendency toward specialization curriculum school compatibility among a sample of students in the first year secondary to She is rude with a sigh Ahmed First November in the city of Alexandria, where the study sample (80) male and female pupils (scientific, literary )The researchers used a questionnaire to collect data after unloading and incorporated into the statistical package for social sciences (spss), on the basis of questions reached the following conclusions: .1The nature of the trend toward specialization in first year secondary school pupils are positive. .2There is a high level of consensus curriculum first year secondary students. .3There are differences in the trend toward specialization curriculum first year secondary students, depending on the specialization (scientific, literary.) .4There are significant differences in the level of the consensus curriculum first year secondary students, depending on the specialization (scientific, literary.) .5There is a statistically significant correlation between the tendency toward specialization curriculum and compatibility of the first year of secondary school pupils